Passé présent. L'antagonisme politique et la chimère d'une communauté réconciliée dans la célébration des fêtes patriotiques en Argentine (2008-2019) - Fernández, Mariano (2022)
Celebrations of civic rituals can be the place of an irreducible tension : having the function of commemorating the continuity of the Nation, and therefore of certifying a form of reconciled community, they are also the moment of expression of immediate social fractures and revising a nation-building narrative. Transcendent instances, on the one hand; moments immanent to the conflicts that mark the functioning of the political systems of the present, on the other hand, and the legitimization of a national project, finally. This article aims to compare Argentina's National Independence Day celebrations during two governments with opposing ideological orientations, focusing on this tension. On the one hand, the two presidential terms of Cristina Fernández de Kirchner (2008-2015), a representative figure of the center-left and usually singled out as a «populist». On the other, the government of Mauricio Macri (2015-2019), representing right-wing and center-right sectors, and self-declared «anti-populist».